Injured Salvator merianae (Teiidae) regenerates six tails in central Argentina - Pelegrin, Nicolas (2016)
Lizards have the ability of regenerate many tissues like nerve cells, part of the mandible, parts of the limb, and most of them can regenerate the tail. Tail autotomy followed by tail regeneration is a strategy widely used in lizards to escape from predators. In some cases tail breaks but it does not detaches completely from the body, leading to a regenerated tail with multiple tips. Here we report the finding of a young individual of Salvator merianae from central Argentina which regenerated six tails after being injured.